Thermoplastics and thermoplastic composites : technical information for plastics users - Biron, Michel (Butterworth-Heinemann, 2007)
Thermoplastics represent appx 90% by weight of all plastics consumed world-wide. We know them mainly in the form of polythenes, polyolefins, polystyrenes, nylons and acrylics. Under different heating conditions and by varying the composition of the plastic it is possible to make many different products with differing properties. This is a decision-making tool and source-book of information for plastics users, providing detailed accounts of the materials used, their economics, the selection of appropriate materials, and the use of thermoplastic resins and their composites. By having this book to hand, you will use the right material in the right way to produce the right product. Provides a quick and pragmatic approach to selecting thermoplastics for the non-specialist plastics user Offers detailed accounts of thermoplastics including economic and technological elements Clear and easy to understand illustrated with figures, tables and graphs throughout.